2013
DOI: 10.1002/cncy.21263
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does nonanalytic reasoning contribute to visual learning in cytopathology?

Abstract: BACKGROUND Acquisition of visual interpretation skills in cytopathology may involve 2 strategies. Analytic strategies require trainees to base their interpretive decisions on carefully considered and often exhaustive cytomorphologic feature lists, a process that can be time‐consuming and inefficient. In contrast, nonanalytic pattern recognition strategies are rarely encouraged during training, even though this approach is characteristic of expert diagnostic behavior. This study evaluated the potential role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In the current investigation, we start with the idea that presenting images in pairs will affect the visual learning process in naive participants, a premise that is supported by the results of our previous study . The use of paired stimuli in perceptual discrimination experiments is an accepted experimental paradigm first developed in the 1960s .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the current investigation, we start with the idea that presenting images in pairs will affect the visual learning process in naive participants, a premise that is supported by the results of our previous study . The use of paired stimuli in perceptual discrimination experiments is an accepted experimental paradigm first developed in the 1960s .…”
Section: Introductionmentioning
confidence: 91%
“…In this paradigm, images are presented only with the labels “normal” or “abnormal” and observers must learn how to extract diagnostically useful information from them, unencumbered by complex diagnostic algorithms. This “nonanalytical” approach to discrimination learning has been shown to be a rapid and effective means of visual learning in cytopathology and in other fields …”
Section: Introductionmentioning
confidence: 99%
“…In other studies, encouraging non-analytic, pattern-recognizing (System 1) reasoning by showing multiple images has also resulted in higher diagnostic accuracy and shorter time to diagnosis. 38 Educational studies of biomedical knowledge transference have found increased transference of concepts if multiple examples are taught rather than a single example, and decreased transference when only the conceptual principle is taught. 39 In our study, group 3 students were provided with the greatest number of examples of the tumor images and, hence, an increased transference was expected.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies such as work by Evered et al [21] use non-specific measures, such as participating physicians' response time, to predict diagnostic accuracy and thus overlook much detailed information from physicians during diagnostic reasoning. We exploit human experts' knowledge to facilitate medical image grouping by applying a methodology that is more objective and automated than current research [21][22][23].…”
Section: Challenges In Language Data Analysis For Domain Knowledge Exmentioning
confidence: 98%
“…We exploit human experts' knowledge to facilitate medical image grouping by applying a methodology that is more objective and automated than current research [21][22][23]. The intuition is that the meaning of a medical image is expected to be mirrored by the spoken narrative of a physician when s/he describes the image during a diagnostic process.…”
Section: Challenges In Language Data Analysis For Domain Knowledge Exmentioning
confidence: 99%